Maternal autoantibody related autism: mechanisms and pathways - Jones, Karen L. (Mol Psychiatry, 2018)
It has been estimated that autism spectrum disorder (ASD) now affects 1 in 59 children in the United States. Although the cause(s) of ASD remain largely unknown, it is becoming increasingly apparent that ASD can no longer be defined simply as a behavioral disorder, but is in effect a rather complex and highly heterogeneous biological disorder. Up until recently the brain was thought to be “immune privileged.” However, it is now known that the immune system plays critical roles in the development and functioning of the brain throughout life. Recent evidence from multiple investigators has illustrated the deleterious role that dysregulation of the maternal immune system during gestation can play in the manifestation of changes in neurodevelopment, resulting in the development of neurobehavioral disorders such as ASD. One potential etiologic pathway through which the maternal immune system can interfere with neurodevelopment is through maternal autoantibodies that recognize proteins in the developing fetal brain. This mechanism of pathogenesis is now thought to lead to a subphenotype of ASD that has been termed maternal autoantibody related (MAR) ASD. This review provides an overview of the current research implicating the presence of brain-reactive maternal autoantibodies as a risk factor for MAR ASD.